Study on Local Feed Resources in LuangPrabang for Mitigating Gas Methane Production in an In Vitro Incubation System - Inthapanya , Sangkhom; Silivong, Phonevilay (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
Feed resources is an important for livestock production as well as the potential benefits in terms of nutritive balance and the body weight improvement by free range smallholder livestock production and to use the science and technology methods. Therefore, this proposes was focused an assessment to identify an undertook the feed resources (source of protein, energy and the roughage) from local feedstuff and agricultural by-products to provide an appropriate feed formula for livestock production and while itstrend to decrease the quantity of methane production from ruminant fermentation. The survey was collected of feed resources at three districts of LuangPrabang province such as Phoukhoun, Phonxai and Phonthong districts. There were divided three feed resources as sources of protein, energy and roughage. The objectives were 1). Analyses: DM, Ash, CP, NDF, ADF and CF issues. 2). The in vitro incubation system: gas production, methane in the gas, DM digestibility and methane per unit substrate. The research was conducted at laboratory of Animal Science department, Faculty of Agriculture and Forest Resource, Souphanouvong University, Lao PDR from November 2015 to April 2016. The feedstuff from three resources indicated: the chemical composition and nutritive values was higher protein content in term of roughage feed resource as Guinea grass and lower for Napier grass. Energy feed resource was higher for broken rice than for cassava root. Protein feed resource was cassava leaf higher than paper mulberry respectively. For in vitro incubation system showed that gas production was increased at the beginning of fermented until 18hours and then was reduced when fermented at 24hours. However, while receiving the methane in the gas was increased by fermentation incubation time. The DM digestibility after 24hours was increased into energy feed resource when compared with protein or roughage feed resource. Methane per unit substrate (ml/g) of roughage feed resource was better value for Guinea grass and Kha grass and was decreased at 42.7%. Energy feed resource was better for corn than cassava root and was reduced to 31.5%. Feed resource for protein was trend to better for Thithonia leaf and was reduced to 33.7% respectively. The feed resources are different reflects to the nutritive value, gas production, DM digestibility and were trended to reduce methane production. Therefore, while providing a feed formula its need to consider as well as the principle of animal feed methods.